Dutch listeners’ responses to Dutch, British and American English accents in three contexts. - Nejjari, Warda; Gerritsen, Marinel; van Hout, Roeland; Planken, Brigitte (Dutch Journal of Applied Linguistics, 2021)
The aim of this study was to assess Dutch listeners’ responses to native-accented Englishes compared with Dutch-accented English in terms of speech understandability and speech evaluations in three professional communication contexts. In a matched-guise experiment Dutch listeners (N=392) responded to a Dutch English, a standard British and American accent in terms of speech understandability (intelligibility, comprehensibility, interpretability) and speaker evaluations (status, affect, dynamism). Dutch listeners evaluated these accents in three communication contexts: Lecture, Audio Tour, Job Pitch. Only context affected speech understandability: comprehensibility and interpretability were higher for the Lecture compared to the Audio Tour and the Job Pitch. Accent only negatively affected status evaluations for Dutch-accented English. Context only evoked more affect in the Audio Tour and the Lecture than in the Job Pitch. Our main conclusion is that Dutch-accented English negatively impacts status, but not understanding, affect and dynamism. Context impacts understanding and affect.